FACTORS RELATED TO DENGUE HEMORRHAGIC FEVER (DHF) PREVENTION BEHAVIOR IN THE COMMUNITY IN THE WORKING AREA OF THE KRAMATWATU HEALTH CENTER, SERANG REGENCY IN 2023 - Pipih Saripah; Ikhlasiah, Marthia (ZILLZELL MEDIA PRIMA, 2024)
Dengue Hemorrhagic Fever is one of the public health problems in Indonesia, because the number of patients and the area of spread is increasing along with increasing mobility and population density. In the last 5 years, the number of cases and infected areas has continued to increase and spread widely and often cause Extraordinary Events. This study aims to determine the factors related to dengue fever prevention behavior in the community in the working area of the Puskesmas Kramatwatu District, Serang Regency in 2023. The type of research is quantitative with Cross Sectional design. Independent variables are education, income, knowledge, and attitude. While the dependent variable is dengue fever prevention behavior. Population is the community in the working area of the puskesmas Kramatwatu District. The sample of 88 people was selected by cluster random sampling in four endemic villages. Statistical tests are performed with Chi-Square test and Logistic Regression Test. The results of statistical tests show that the majority of respondents have poor behavior (66.3%). The Chi Square test found that the variables of education, knowledge, and attitude obtained a value of p<0.05 there was a significant relationship with dengue fever prevention behavior, while the income variable obtained a value of p>0.05 there was no significant relationship with dengue fever prevention behavior. In the logistic regression test, it is known that the biggest variable affecting dengue prevention behavior is the knowledge variable with an Odd Ratio value = 4.8.